Synthesis, Characterization and Antibacterial Studies of (3,3-Dimethyl-7-oxo-6-(2-phenylacetamido)-4-thia-1-azabicyclo[3.2.0]heptane-2-carboxylic acid-Cr (III) Complex - Otuokere, Ifeanyi Edozie; Robert, Unwanaobong Friday (Journal of Nepal Chemical Society, 2020)
Benzylpenicillin, also known as (3,3-Dimethyl-7-oxo-6-(2-phenylacetamido)-4-thia-1-azabicyclo[3.2.0]heptane-2-carboxylic, is a common bactericidal antibiotic of the betalactamin family which is mostly used to treat infections caused by gram-positive bacterial strains and few gram-negative bacterial strains. Cr (III) complex of benzylpenicillin was synthesized by the reaction of benzylpenicillin with CrCl3.6H2O. The structure of the complex was confirmed through elemental analysis, electrical conductivity, FT-IR, electronic spectra, 1H-NMR, and 13C-NMR spectroscopic methods. The physical properties such as solubility, color and melting point were also determined for both the ligand and the complex. The complex has a deep green color. Both the ligand and the complex are ionic (236.0 and 126.0 Sm2.mol-1). From the spectroscopic result, the ligand behaved as a pentadentate ligand coordinating to the metal ion through OH, NH, C=O of amide, carboxylate& β-lactam. A trigonal bipyramidal geometry has been proposed for the metal complex. The prepared complex was evaluated in vitro for its antibacterial activity against some pathogenic gram-positive (Staphylococcus aureus, Bacillus substilis, Bacillus cereus, and Enterococcus faecalis) and gram-negative bacteria (Escherichia coli, Enterobacter cloacae, Pneumonia aeruginosa and Campylobacter fetus). The metal complex showed enhanced antibacterial activity as compared to the uncomplexed ligand.